2012
DOI: 10.1002/ajmg.a.35263
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy improves joint motion and outcome of the 12‐min walk test in a mucopolysaccharidosis type VI patient previously treated with bone marrow transplantation

Abstract: Mucopolysaccharidosis type VI (MPS VI; Maroteaux-Lamy syndrome, OMIM #253200) is a rare disorder involving multiple organs and manifested particularly by severe skeletal abnormalities. Bone marrow transplantation (BMT) improves cardiopulmonary function and facial features, but has limited success in ameliorating skeletal abnormalities and short stature. Here, we report the outcome of enzyme replacement therapy (ERT) with recombinant human arylsulfatase-B (ASB, Naglazyme, BioMarin, Novato, CA) in an MPS VI pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…They presented reduced maximal speed, increased motionless time, and reduced distance traveled, but none of these effects were statistically significant. This suggests that the affected rats' walking ability, unlike that of human patients893839 was relatively preserved at this age. However, affected animals were extremely impaired in vertical activity, especially when forced to stand on their hindlimbs without any forelimb support (rearing), and it has been shown to be one of the most affected behavioral parameters in animal models of osteoarthritis3435.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…They presented reduced maximal speed, increased motionless time, and reduced distance traveled, but none of these effects were statistically significant. This suggests that the affected rats' walking ability, unlike that of human patients893839 was relatively preserved at this age. However, affected animals were extremely impaired in vertical activity, especially when forced to stand on their hindlimbs without any forelimb support (rearing), and it has been shown to be one of the most affected behavioral parameters in animal models of osteoarthritis3435.…”
Section: Discussionmentioning
confidence: 88%
“…The effects of ERT in MPS VI patients are generally evaluated only on the 6–12 min walking test or climb test, and it is generally reported to improve these behavioral functions as well as urinary GAG levels793849. Nevertheless, when more detailed behavioral analysis is performed, using for instance joint motility scores, some of the therapeutic limits of ERT are generally unrevealed638.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have evaluated the impact of the disease on skeletal muscle have used functional tests such as the 6- or 12-minute walk test, 3-min stair-climb, and/or goniometric tests for joint mobility evaluation [2,6,7,13]. Cardoso-Santos and colleagues measured hand grip strength in MPS VI patients and reported that 23 out of the 26 patients tested could not generate enough pressure to activate the dynamometer resulting in a reading of zero pounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the currently available therapies of hematopoietic cell transplantation (HCT) and/or enzyme replacement therapy (ERT), we hypothesized that all MPS subgroups studied would have decreased strength compared to the control group due to the involvement of the musculoskeletal system in MPS disease progression. Based on the severity of the MPS IH phenotype, it was suspected that MPS IH would have the greatest difference in skeletal muscle strength [1,11,16], while MPS VI and MPS IA groups would have significantly less strength than controls but more strength than the MPS IH group as a result of less neurologic involvement [1,2,13]. Finally, as would be expected based on the mode of inheritance [1], all of our MPS II subjects are male.…”
Section: Introductionmentioning
confidence: 99%